Strategi dan Metode Efektif dalam Pembelajaran Bahasa Arab untuk Anak Usia 5-6 Tahun pada Pendidkan Anak Usia Dini - Zahra, Sofia; Tasya, Luthfiyyah; Dinanti Lubis, Dea; Zahra Lubis, Hilda (Al Fitrah: Journal Of Early Childhood Islamic Education, 2025)
It is important for children to learn a foreign language from an early age, one of which is Arabic. However, to obtain information, experience, and the ability to learn Arabic, it is essential to choose effective strategies and methods for children in learning Arabic. Because learning strategies and methods are essential components in learning, they must be adapted to the child's developmental stage. This study aims to identify various effective strategies and methods in learning Arabic for children aged 5-6 years. This research is a qualitative study with a descriptive research type. Data collection in this study was through data obtained from journals, books, and related articles. The results of the study indicate that effective Arabic learning strategies include direct strategies such as memory, cognition, and compensation, as well as indirect strategies such as metacognitive, affective, and social. In addition, effective methods in learning Arabic also include singing, writing, memorization, and play. By integrating creative and interesting strategies and methods, learning Arabic certainly becomes enjoyable for children.